The structural and conductivity characterization of p2o5-mgo-tio2-li2o glass ceramic embedded with nickel nanoparticles - Abd. Rahman, Sharifah Fahsuhaizam (TRANS TECH PUBLICATIONS, 2016)
Melt quenching technique (MQT) has been used to prepare the series of 75P2O5-17MgO- (3-x)TiO2-5Li2O glasses doped Nickel nanoparticles (x = 0, 0.5, 1.0, 1.5, 2.0, 2.5, 3.0), which was converted into glass-ceramic through heat treatment at 350 °C. In this study, the effects of NiO nanoparticle addition and heat treatment on microstructure were investigated through DTA and XRD. The frequency-dependent electrical data were used to study the conductivity mechanism. Preliminary experimental results from DTA measurement showed that the stability of the glasses are increased when the increment of TiO2 in the glasses. The XRD results showed the completely amorphous products were prepared by MQT and crystallite structured of glass ceramic were obtained via further heat treatment. Upon the increment of temperature, conductivities increased significantly.